Mitochondria in innate immunity signaling and its therapeutic implications in autoimmune diseases - Jiao, Yuhao; Yan, Zhiyu; Yang, Aiming (Frontiers in Immunology, 2023)
Autoimmune diseases are characterized by vast alterations in immune responses, but the pathogenesis remains sophisticated and yet to be fully elucidated. Multiple mechanisms regulating cell differentiation, maturation, and death are critical, among which mitochondria-related cellular organelle functions have recently gained accumulating attention. Mitochondria, as a highly preserved organelle in eukaryotes, have crucial roles in the cellular response to both exogenous and endogenous stress beyond their fundamental functions in chemical energy conversion. In this review, we aim to summarize recent findings on the function of mitochondria in the innate immune response and its aberrancy in autoimmune diseases such as rheumatoid arthritis, systemic lupus erythematosus, etc., mainly focusing on its direct impact on cellular metabolism and its machinery on regulating immune response signaling pathways. More importantly, we summarize the status quo of potential therapeutic targets found in the mitochondrial regulation in the setting of autoimmune diseases and wish to shed light on future studies.